A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages 1. National Minimum Scales and Grading Resident Nursing Staffs. Average number of beds in daily occupation. Staff Nurse after termination of Agreement Ward Sister Special Sisters, (Theatre, X-ray, Maternity, Massage, etc.) Home Sister Sister House- keeper Night Supt. Asst. Matron Matron (Annual increment £5) (Annual increment £10) (Annual increment £10) (Annual increment £10) (Annual increment £10) (Annual increment £15) (Annual increment £20) £ £ £ £ £ £ £ Under 25 75-95 95-135 120-160 — — — 150-190 25- 50 75-95 95-135 120-160 — 120-170 120-180 200-240 50-100 75-95 95-135 120-160 120-160 120-170 120-180 250-290 100-200 75-95 95-135 120-160 120-160 120-180 140-215 300-340 200-300 75-95 95-135 120-160 140-180 140-190 140-230 350-410 300-500 75-95 95-135 120-160 140-180 140-190 160-270 400-480 Above 500 75-95 95-135 120-160 140-180 140-190 180-290 500-580 General and Children. Tuberculosis and/or Fever Probationers : First year............ £35 £45 Second year ......... £40 £50 Third year ... £50 — Fourth year £60 — Sister Tutors : £160— £15 -£265 (certificated King’s College for Women, or other approved college). For special posts, e.g., Almoners, Dieticians, Dispensers, Masseuses, Pharmacists, etc., some of which are resident positions, others non-resident, special scales of salaries should be applicable. The scale minimum of a Staff Nurse to be paid on obtaining the final certificate. The salaries for Resident Staff are exclusive of emoluments. The value of emoluments (assessed at outside market value) should be added to salary of nurses living outside the hospital. 7 292/54.73/2/1